Spatial release from masking in the median plane with nonnative speakers using individual and mannequin head related transfer functions - González-Toledo, Daniel; Cuevas-Rodríguez, María; Vicente, Thibault; Picinali, Lorenzo; Molina-Tanco, Luis; Reyes-Lecuona, Arcadio (AIP, 2024)
Spatial release from masking (SRM) in speech-on-speech tasks has been widely studied in the horizontal plane, where interaural cues play a fundamental role. Several studies have also observed SRM for sources located in the median plane, where (monaural) spectral cues are more important. However, a relatively unexplored research question concerns the impact of head-related transfer function (HRTF) personalisation on SRM, for example, whether using individually-measured HRTFs results in better performance if compared with the use of mannequin HRTFs. This study compares SRM in the median plane in a speech-on-speech virtual task rendered using both individual and mannequin HRTFs. SRM is obtained using English sentences with non-native English speakers. Our participants show lower SRM performances compared to those found by others using native English participants. Furthermore, SRM is significantly larger when the source is spatialised using the individual HRTF, and this effect is more marked for those with lower English proficiency. Further analyses using a spectral distortion metric and the estimation of the better-ear effect, show that the observed SRM can only partially be explained by HRTF-specific factors and that the effect of the familiarity with individual spatial cues is likely to be the most significant element driving these results.
Keywords: Comunicación oral; Micrófonos; Reconocimiento automático del lenguaje; Transductores electroacústicos; Procesado de señales; Electrónica - Aparatos e instrumentos; Intercomprensión (Lingüística); Speech communication; Head related transfer function; Cross language speech; Microphones; Auditory system; Speech intelligibility; Speech recognition; Monaural; Acoustic transducers; Signal processing